Analysis of planetary boundary layer characteristics of sandstorm based on vertical observation - Bao, Leer; Yang, Jiaqi; Xiao, Nan (Frontiers in Environmental Science, 2025)
As a meteorological disaster, sandstorm largely impacts on the human society and the natural environment and has been receiving increasing attention. The planetary boundary layer is a key area connecting the surface and the free atmosphere, and its structure and change play a decisive role in the occurrence, development and dissipation of sandstorms. However, the theories and methods of synoptic and meteorological disciplines are mainly used to study the characteristics and causes of sandstorm process, while mesoscale analysis methods such as vertical variation characteristics of high-altitude wind field and atmospheric circulation characteristics are rarely used to study the process and causes of sandstorm. In this study, the change characteristics of planetary boundary layer of a sandstorm were analyzed by using vertical observation. The results showed that: 1) the downward transfer of momentum and the abrupt change in wind speed are the key indicators indicating the occurrence of sandstorms. The explosive downward movement of the cold advection in the lower layer strengthens the lifting of the warm advection, providing a powerful driving force for the occurrence of severe sandstorms. 2) Monitoring changes in the frontogenesis function provides a new perspective for predicting severe sandstorms. By analyzing the frontogenesis function, the dynamic and thermal conditions of the atmosphere can be understood. The potential for sandstorm occurrence can be assessed, and the severity of sandstorms can be predicted. 3) The formation of the dry atmospheric junction and the inversion layer affected the initiation, transportation, and deposition processes of sand and dust. The vertical distribution characteristics of the extinction coefficient and the depolarization ratio, showed the enhancement of turbulent activities during the sandstorm, which is another important characteristic of the changes in the PBL during the sandstorm. The results of the study will help to improve the understanding of sandstorms, provide a scientific basis for their monitoring, forecasting and prevention, and support the development of effective environmental management and mitigation strategies.